Motion-based super-resolution in the peripheral visual field - Patrick, Jonathan A.; Roach, Neil W.; McGraw, Paul V. (Association for Research in Vision and Ophthalmology, 2017)
Improvements in foveal acuity for moving targets have been interpreted as evidence for the ability of the visual system to combine information over space and time, in order to reconstruct the image at a higher resolution (super-resolution). Here, we directly test whether this occurs in the peripheral visual field and discuss its potential for improving functional capacity in ocular disease. The effect of motion on visual acuity was first compared under conditions in which performance was limited either by natural undersampling in the retinal periphery or by the presence of overlaid masks with opaque elements to simulate retinal loss. To equate the information content of moving and static sequences, we next manipulated the dynamic properties of the masks. Finally, we determined the dependence of motion-related improvements on the object of motion (target or mask) and its trajectory (smooth or jittered). Motion improved visual acuity for masked but not unmasked peripheral targets. Equating the information content of moving and static conditions removed some but not all of this benefit. Residual motion-related improvements were largest in conditions in which the target moved along a consistent and predictable path. Our results show that motion can improve peripheral acuity in situations in which performance is limited by abnormal undersampling. These findings are consistent with the operation of a super-resolution system and could have important implications for any pathology that alters the regular sampling properties of the retinal mosaic.